HUBUNGAN BEBAN KERJA TERHADAP KINERJA PEGAWAI DI INSTANSI SATUAN POLISI PAMONG PRAJA PROVINSI JAWA BARAT TAHUN 2022 - Givani Putri Amanda Pramono (2023)
One of the problems that can affect someone's occupational health is workload. Shortage of manpower against job demands can affect workload. It was recorded in January 2021 that there was a 4.1% decrease number of civil servants from the previous year. High workload can causes fatigue, illness, and decreased concentration so those can have an impact on the work's quality. This study aims to determine the relationship between workload to performance of Civil Service Police West Java Province Unit This study used a cross-sectional design. Data was collected using questionnaire. The population of this study were all employees of the Civil Service Polis West Java Province Unit which was 92 people using total sampling technique. Data were analyzed using chi square test. Univariate analysis results showed that 50 respondents (54,3%) had a heavy workload and 48 respondents (52,2%) had good performance. The results of bivariate test showed that there is a relationship between workload to performance (p = 0,000) and the heavier the workload, 6,8 times will reduce performance. These results indicate that the heavier the workload, the lower someone's performance will be.